Tipo de secagem e armazenamento na qualidade de sementes de Jatropha curcas L. - Neunfeld, Tania Helena (2012)
The economic importance of biofuels in the Brazilian national scene has increased interest in crops such as physic nut. The study aimed to determine the effects of drying, environment and period of storage in fruits and seeds of Jatropha curcas L. and the interference of these variables in seed quality. The experiment was conducted at the Laboratory of Technology of Seeds and Seedlings of the Western Parana State University during May 2010 to September 2011. The fruits were collected at Dourados, Mato Grosso do Sul. Treatments consisted of four types of drying: 1) dry physic nut fruits to sun, 2) dry physic nut fruits to shade, 3) seeds drying in the sun, 4) seeds drying in the shade; and two storage environments: a) laboratory storage (not controlled atmospheric conditions) and b) cold storage (temperature 14 ± 2 ° C and relative humidity of 65-80%). The storage period was 15 months. The experimental design was a completely randomized in factorial scheme 4x2x6. We carried out a morphometric characterization of Jatropha curcas seeds (length, width and thickness) as well as weight of a thousand seeds and moisture content, percentage of normal seeds germinated in a substrate rollpaper, the germination speed, and tetrazolium test for the indication of the physiological potential of the seed lot; performing evaluations are equidistant from three months of storage (zero months - not stored seeds, three, six , nine, twelve and fifteen months). The data were subjected to statistical evaluation by SISVAR and GENES programs. The results indicated that drying should preferably be performed in the absence of fruit, whether the sun or shade and storage, especially for long periods, should not occur in an environment of high humidity as this in cold conditions in this study